Percutaneous pulmonary valve implantation for free pulmonary regurgitation following conduit-free surgery of the right ventricular outflow tract. (1st May 2015) - Cools, Bjorn; Brown, Stephen C.; Heying, Ruth; Jansen, Katrijn; Boshoff, Derize E.; Budts, Werner; Gewillig, Marc
Abstract: Introduction: Pulmonary regurgitation (PR) following surgery of the right ventricular outflow tract (RVOT) is not innocent and leads to significant right heart dysfunction over time. Recent studies have demonstrated that percutaneous valves can be implanted in conduit free outflow tracts with good outcomes. Objectives: To evaluate in patients with severe PR – anticipated to require future pulmonary valve replacement – the feasibility and safety of pre-stenting dilated non-stenotic patched conduit-free right ventricular outflow tracts before excessive dilation occurs, followed by percutaneous pulmonary valve implantation (PPVI). Patients and methods: Twenty seven patients were evaluated, but only 23 were deemed suitable based on the presence of an adequate retention zone ≤ 24 mm defined by semi-compliant balloon interrogation of the RVOT. A 2 step procedure was performed: first the landing zone was prepared by deploying a bare stent, followed 2 months later by valve implantation. Results: RVOT pre-stenting with an open cell bare metal stent (Andrastent XXL range) was performed at a median age of 13.0 years (range: 6.0–44.9) with a median weight of 44.3 kg (range: 20.0–88.0). Ninety six percent (22/23) of patients proceeded to PPVI a median of 2.4 months (range: 1.4–3.4) after initial pre-stent placement. Twenty one Melody valves and one 26 mm Edwards SAPIEN™ valve were implanted. Complications consisted of embolization of prestent (n = 1), scrunching (n = 4) and mild stent dislocation (n = 2). During follow-up, no stent fractures were observed and right ventricular dimensions decreased significantly. Conclusions: Post-surgical conduit-free non-stenotic RVOT with free pulmonary regurgitation can be treated percutaneously with a valved stent if anatomical (predominantly size) criteria are met. In experienced hands, the technique is feasible with low morbidity. Highlights: A patched right ventricular outflow tract frequently leads to severe pulmonary regurgitation. A patched RVOT can be managed to allow successful percutaneous valve implantation. A prestented right ventricular outflow tract is a good landing zone for a valved stent. Balloon interrogation of the conduit free landing zone is essential to determine stent size.